2017
DOI: 10.1002/clc.22782
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban, rivaroxaban, and dabigatran use in patients undergoing catheter ablation for atrial fibrillation using the second‐generation cryoballoon

Abstract: Background Data are limited on the safety of periprocedural anticoagulation with novel oral anticoagulants (NOACs) in patients undergoing pulmonary vein isolation (PVI) using the second‐generation cryoballoon (CB) for the treatment of atrial fibrillation. Hypothesis We hypothesized that the incidence of acute periprocedural complications in patients undergoing PVI do not differ between patients treated with VKA compared to NOACs. Methods In 200 consecutive patients (mean age, 64.3 _ 10.6 years; female, n = 83)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Despite high rate of silent cerebral embolic lesions, the incidence of TIA or stroke has been reported lower than 1% [108] . To decrease thromboembolic complications of ablation, uninterrupted anticoagulation strategy should be preferred compared with bridging strategies using heparin or enoxaparin regardles of used anticoagulant agent [109,110] . To reveal the presence of thrombus formation in the LAA, routine usage of transesophageal echocardiography is recommended by some authors.…”
Section: Figurementioning
confidence: 99%
“…Despite high rate of silent cerebral embolic lesions, the incidence of TIA or stroke has been reported lower than 1% [108] . To decrease thromboembolic complications of ablation, uninterrupted anticoagulation strategy should be preferred compared with bridging strategies using heparin or enoxaparin regardles of used anticoagulant agent [109,110] . To reveal the presence of thrombus formation in the LAA, routine usage of transesophageal echocardiography is recommended by some authors.…”
Section: Figurementioning
confidence: 99%
“…With the advent of direct oral anticoagulants (DOACs), an increasing number of patients with AF undergo CA with DOAC ther-apy. Recent randomized clinical trials (RCTs) [5][6][7][8][9] , cohort studies [10][11][12] , and meta-analyses [13][14][15] have showed that uninterrupted or minimally interrupted DOACs are associated with lower or non-inferior risk of bleeding and thromboembolic events compared with uninterrupted warfarin. The 2017 consensus statement on AF ablation [1] recommends performing CA without anticoagulant interruption with warfarin or dabigatran (class I); however, it also stated that holding 1 to 2 doses of DOAC prior to CA is reasonable (class IIa).…”
Section: Introductionmentioning
confidence: 99%
“…Although a few recent studies report that uninterrupted DOAC therapy during AF ablation is feasible and safe, the critical point of intraprocedural anticoagulation management has not been addressed and protocols on UFH administration and ACT monitoring are lacking. [6][7][8][9] However, several arguments support that UFH management cannot be directly extrapolated from VKA-treated patients: the initial level of anticoagulation varies according to DOAC concentration, DOAC interferes with the ACT, and the sensitivity of the ACT to DOAC as well as the response to UFH administration in DOAC-treated patients strongly differ from that of VKA-treated patients and also among DOACs. 10,11 This study aims to illustrate intraprocedural UFH management complexity in uninterrupted DOAC-treated patients.…”
Section: Introductionmentioning
confidence: 99%
“…In uninterrupted DOAC–treated patients, the same ACT ≥300 seconds usually proposed for intraprocedural UFH is based on very limited evidence, mostly extrapolated from VKA‐treated populations. Although a few recent studies report that uninterrupted DOAC therapy during AF ablation is feasible and safe, the critical point of intraprocedural anticoagulation management has not been addressed and protocols on UFH administration and ACT monitoring are lacking . However, several arguments support that UFH management cannot be directly extrapolated from VKA‐treated patients: the initial level of anticoagulation varies according to DOAC concentration, DOAC interferes with the ACT, and the sensitivity of the ACT to DOAC as well as the response to UFH administration in DOAC‐treated patients strongly differ from that of VKA‐treated patients and also among DOACs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation